Electric fields and currents in the detached regime of a tokamak1. Issue 6 (9th May 2018) - Rozhansky, V.; Kaveeva, E.; Senichenkov, I.; Sytova, E.; Veselova, I.; Voskoboynikov, S.; Coster, D.
Abstract : The structure of currents and electric fields in the edge tokamak plasma is analysed for detached regimes of a tokamak. Strong electric fields in the divertor regions and near the X‐point are typical for detached regimes. It is shown that the value of the poloidal electric field in the regions with the temperature 1–2 eV is determined by the Spitzer conductivity and parallel currents. The latter are a combination of thermal and Pfirsch–Schlüter (PS) currents. The E × B drifts have a significant impact on the distribution of the plasma in the divertor. Stability of the detached regimes with strong electric fields is also analysed. It has been demonstrated that the so‐called PS instability caused by PS current can develop in the cold low‐temperature regions of the detached divertor.